The Interpretation of an Indonesian Ancient Martial Art: An Analysis of Pencak Silat from The Lens of Clifford Geertz’s Blurred Genres - Herujiyanto, Lukas Henggara Nandamai; Setyawan, Agustinus Hary ((JELE) Journal Of English Language and Education, 2024)
This article delves into the interpretation of Pencak Silat, an ancient Indonesian martial art, through the lens of Clifford Geertz's concept of "Blurred Genres." Pencak Silat encompasses a wide array of traditional and modern martial art genres, practiced individually or in duels, with or without musical accompaniment. The study focuses on the cultural, social, and political dimensions of Pencak Silat, particularly its impact on Indonesian society. The article establishes the historical roots of Pencak Silat in Old Malay culture, evolving from the Buddhist-Hindu kingdom of Sriwijaya (seventh to eleventh centuries CE). It explores the martial art's role in shaping national identity during President Soeharto's New Order regime. Pencak Silat served as a vehicle for the promotion of national identity and New Order citizenship. The analysis employs Geertz's three major analogies—Game, Drama, and Text—to interpret Pencak Silat. As a "body cultivation," Silat's presence aligns well with Geertz's tools for interpreting anthropological phenomena.